Effect of integrated nutrient management on dry herbage yield, nutrient uptake and profitability of French Basil (Ocimum basilicum L.) - Baraa AL Mansour (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2017)
Field experiments were conducted at ICAR - Indian Institute of Horticultural Research, Bengaluru during Kharif season of 2015 and 2016 with nine treatments and three replications in a randomized block design to find out the effect of integrated nutrient management on dry herbage yield, nutrient uptake and economics of sweet basil (Ocimum basilicum). The results revealed that the conjunctive use of inorganic fertilizer along with FYM increased the dry herbage yield and nutrient uptake of sweet basil. Application of recommended FYM (10 t/ha) along with recommended NPK (160:80:80 kg/ha) registered the highest dry herbage yield (8.43 and 3.76 t ha- 1) in the main crop and ratoon, respectively and maximum uptake of nutrient in the main crop as N (155.67 and 113.19 kg/ha), P (43.80 and 32.43 kg/ha) and K (163.33 and 116.16 kg/ha) and in ratoon (56.43 and 26.65 kg ha-1), (16.14 and 14.01 kg ha-1) and (55.65 and 39.27 kg ha-1) in 2015 and 2016 respectively. Highest B: C ratio (5.49) was obtained with application of full dose of recommended NPK fertilizer during 2015. While in 2016, the maximum B: C ratio (3.71) was recorded with application of recommended dose of NPK (160:80:80 kg/ha) + FYM (10 t/ha).